Reinterpreting and Reforming the City: Patrimonialization, Cosmopolitanisms, and the Ethnography of the Heritage-Scape in Damascus - Copertino, Domenico (Ethnologies, 2013)
Concepts and practices of patrimonialisation in the Middle East, although primarily imported from Europe during the last phase of Ottoman rule and the colonial mandate/period, have been reinterpreted and given new meanings and aims in the postcolonial era. I investigate a local re-conceptualisation of heritage practice, put forward by Damascenes involved in the heritage policies of Syria’s capital city. I also focus on the marginalisation of groups of people considered unfit to be part of the heritage, which is a common outcome of patrimonialisation. Finally, I explore some questions related to the ethnographical study of the global social spaces that are frequently labeled as “heritage-scapes.”